UMER CHAPRA'S ISLAMIC ECONOMIC PHILOSOPHY AND RELEVANCE WITH FINANCIAL TECHNOLOGY - rifqi khairul anam (JSE: Jurnal Sharia Economica, 2024)
This research explores the intersection of artificial intelligence in financial technology and Umer Chapra's Islamic economic philosophy, focusing on ethical implications. Through a qualitative descriptive approach and comprehensive literature review, the study analyzes how AI-powered financial systems can be designed and implemented to uphold the Maqasid al-Shariah, emphasizing justice, equity, social responsibility, and fulfillment of human needs. Findings suggest that AI has the potential to enhance financial decision-making, promote ethical conduct, and address social issues like poverty and unemployment, aligning with Chapra's principles by improving credit assessments, fraud detection, and personalized financial advice. The study concludes that integrating AI in Fintech with the Maqasid offers an opportunity for greater economic stability and social responsibility by prioritizing the preservation of religion, life, intellect, lineage, and property, while acknowledging the need for robust governance frameworks to mitigate potential ethical challenges and ensure responsible AI development.